Stress and wellness paradigms among educators in diverse academic contexts in Spain, Colombia and Chile - Peris-Ramos, Helia Carmen; David-Fernandez, Susana; Beltrán-Velasco, Ana Isabel; Yáñez-Sepúlveda, Rodrigo; López-Gil, José Francisco; Clemente-Suárez, Vicente Javier (Frontiers in Education, 2025)
ObjectiveThis study analyze the relationship between stress and wellness among educators, analyzing data from 1,037 active teachers across various academic settings. This study has a dual objective: firstly, to analyze the psychological differences among teachers to identify the impact of stress determinants that are prevalent across various academic disciplines; and secondly, to examine the correlation between the psychological profiles of these professionals and their respective teaching domains.MethodsTo achieve our research objectives, we conducted a study with a unique combination of methodologies, incorporating cross-sectional and retrospective approaches. Initially, we collected data through an online survey distributed through Google Docs for 4 months in the 2020–2021 school year, targeting a representative population of in-service teachers aged between 20 and 70 years (mean age ± standard deviation: 41 ± 9.2 years). Subsequently, different predefined variables were evaluated that studied current conditions such as retrospective evaluations of past data. The research assesses key variables such as teaching experience, teacher satisfaction, loneliness, perceived stress, and various psychological dimensions. SPSS 24.0 was used to analyze the data using descriptive statistics, normality tests, ANOVA with Tukey’s post hoc and Pearson’s correlation, with a significance level of p ≤ 0.05 to ensure a thorough and rigorous approach in the analysis.ResultsThe sample consisted of 40.1% men and 59.9% women, with a mean age of 41.0 ± 9.2 years in Spain, Colombia and Chile and a mean teaching experience of 12 years (12.1 ± 8.9 years). In particular, significant differences in stress indicators were observed, particularly among health sciences and engineering/architecture educators compared to their counterparts in the biological and physical sciences; Engineering/architecture teachers demonstrated higher levels of depersonalization and loneliness compared to biological and physical science teachers. On the other hand, health sciences teachers stand out for higher levels of perceived stress, loneliness and conscientiousness. No significant differences were found between the educational branches in aspects such as teacher satisfaction, work stress, emotional exhaustion, personal fulfillment or traits such as extraversion and openness.ConclusionThe study analyzes the determinants of stress in different academic disciplines, highlighting the significant influence of teaching fields on teachers’ levels of stress, depersonalization, and loneliness. In addition, the interaction between psychological profiles and academic domains is highlighted, as well as the psychosocial risks associated with certain disciplines. The findings suggest the need to implement adapted mental health frameworks in educational institutions and advocate for personalized and multidimensional interventions with specific strategies with the aim of improving teachers’ well-being and, consequently, the quality and sustainability of education.